Effects of emission sources on the particle number size distribution of ambient air in the residential area. (15th January 2023) - Harni, Sami D.; Saarikoski, Sanna; Kuula, Joel; Helin, Aku; Aurela, Minna; Niemi, Jarkko V.; Kousa, Anu; Rönkkö, Topi; Timonen, Hilkka
Abstract: Particle size distribution is a major factor in the health and climate effects of ambient aerosols, and it shows a large variation depending on the prevailing atmospheric emission sources. In this work, the particle number size distributions of ambient air were investigated at a suburban detached housing area in northern Helsinki, Finland, during a half-year period from winter to summer of 2020. The measurements were conducted with a scanning mobility particle sizer (SMPS) with a particle size range of 16–698 nm (mobility diameter), and the events with a dominant particle source were identified systematically from the data based on the time of the day and different particle physical and chemical properties. During the measurement period, four different types of events with a dominant contribution from either wood-burning (WB), traffic (TRA), secondary biogenic (BIO), or long-range transported (LRT) aerosol were observed. The particle size was the largest for the LRT events followed by BIO, WB, and TRA events with the geometric mean diameters of 72, 62, 57, and 41 nm, respectively. BIO and LRT produced the largest particle mode sizes followed by WB, and TRA with the modes of 69, 69, 46, and 25 nm, respectively. Each event type had also a noticeably different shape of the average number size distribution (NSD). In addition to the evaluation of NSDs representing different particle sources, also the effects of COVID-19 lockdown on specific aerosol properties were studied as during the measurement period the COVID-19 restrictions took place greatly reducing the traffic volumes in the Helsinki area in the spring of 2020. These restrictions had a significant contribution to reducing the concentrations of NOx and black carbon originating from fossil fuel combustion concentration, but insignificant effects on other studied variables such as number concentration and size distribution or particle mass concentrations (PM1, PM2.5, or PM10 ). Highlights: Events with a dominant particle source were identified systematically from ambient data. Particle sources were traffic, biomass combustion, biogenic and long-range transport. Number size distributions from different sources had different shapes. Traffic produced significantly smaller particles compared to wood combustion. Particle number size distribution from wood-burning showed large variability.